ANALISIS BISNIS DALAM PERENCANAAN STRATEGIS SISTEM INFORMASI PADA PD. INDRASARI - Sumardiono Sumardiono (Jurnal Informatika, 2020)
The development of modern trade is strongly influenced by advances and conveniences in information systems. Business and marketing services are supportive of accessing the digital world, which we usually know as e-shop or e-commerce. E-commerce is virtual in the sense that it exists on the Internet, and physical existence outside the Internet is limited (Azam 2012)[1]. PD. Indrasari is a home-based business or IKM whose scope of business is still conventional, meaning that business and business applications are still manual without the interference of information technology.Research in PD. Indrasari is only in its external business environment, so researchers use the method described by Ward and Peppard to obtain a business strategy. The methods are PEST analysis, PEST analysis (political, economic, social and technological)[2] and Five Porter Forces analysis The Porter’s Five Forces Model includes Bargaining power of suppliers, bargaining power of buyers, threat of new entrants, and threat of substitutes [3].With this PEST analysis to determine the condition of governance / regulation, economy, social and technology in the area of research object and the Five Porter Forces analysis to determine competition in terms of production and marketing needs. By knowing some of the results of the analysis, it will be formulated as a component in the planning of an information system strategy, in order to obtain recommendations for information systems and applications that will be implemented based on the planned time.